New standard methodology in cleaner production for small & medium industries / Razuana Rahim - Razuana, Rahim (2017)
Many countries are taking initiatives to reduce greenhouse gases emission, mainly carbon dioxide (CO2) due to growing pressure to tackle global warming effects. There are many strategies available for this purpose. Cleaner Production (CP) is one of the main strategies that can be considered to reduce greenhouse gases and it is a powerful tool for greening the industries. However, the strategy is not widely used because there is no systematic implementation methodology for industries with minimum expertise requirement. Therefore, in this work, a new methodology for conducting a CP audit was developed by taking into consideration various CO2 generating activities and processes in a typical manufacturing premise. Subsequently, the methodology was used to gather information. The CP audit tool proposed consisted of 17 key components including quantification of entities that contribute to the generation of CO2 emission, which are water, electricity and fuel consumption together with solid waste and wastewater generation. The gathered information was analysed and the major contributors for CO2 emissions were identified and estimated. Subsequently, systematic CP option generation and prioritization methodology were developed. The CP option generation tool comprised investigative questions that were developed according to the 17 components in the CP audit tool, whereas the answers for the questions would guide the CP options generation. The options were generated based on the changes or modifications in the operation, design, materials, housekeeping, recycling and training. The options generated were further evaluated and prioritized in terms of economic, environmental and other tangible and intangible returns. The economic evaluation showed the payback period for the CP options, while the environmental evaluation estimated the CO2 reduction quantitatively. The practicality of the methodology developed was then validated through demonstration in three case studied manufacturing premises, which are printing, plastic resin and beverage. The premises were selected due to their significant contribution to environmental issues in Malaysia. Major CO2 emission contributors in each of the premise were identified and estimated per unit of product. The CP audit tool developed was able to comprehensively cover the overall activities and processes in the premises. The estimated CO2e generation in the printing, plastic resin and beverage premises were 0.81 kg CO2e/kg of paper processed, 0.84 kg CO2e/kg of resin and 0.07 kg CO2e/L of beverage, respectively. Various CP options were generated, evaluated and prioritized accordingly for these premises. From this analysis, it can be concluded that it is possible to reduce CO2 emission by 10-15% even without any monetary investment by administrating the identified CP options. In addition, about 5-10% of the CP options implemented with monetary commitment could be recovered within a year. Furthermore, it is confirmed that the CP audit, CP option and CP evaluation tools developed could be used to initiate a greening program for Small and Medium Industries.